HIV Epidemic in Tanzania: The Possible Role of the Key Populations - Bonaventura C. T. Mpondo; Daniel W. Gunda; Semvua B. Kilonzo (AIDS Research and Treatment)
HIV remains a public health concern in Tanzania and other Eastern and Southern African countries. Estimates show that there were about 1.4 million people living with HIV in Tanzania in the year 2013. HIV is a generalized epidemic in Tanzania with heterosexual transmission being the main route of transmission. Recently, however, there has been growing concern on the potential role of the key populations in HIV epidemic in the country. Studies done have shown significantly higher HIV prevalence in these populations compared to the general population. These studies have also reported high risky behaviors among members of these populations. This review aims at discussing the possible role of the key populations in the HIV epidemic in Tanzania.